Crystallization and preliminary X-ray characterization of a thermostable low-molecular-weight 1,4-beta-D-glucan glucohydrolase from an alkalothermophilic thermomonospora sp. - Manikandan, K.; Jagtap, Sharmili; Rao, M.; Ramakumar, S. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2006)
{Cellulases catalyze the hydrolysis of beta-1,4-glycosidic linkages within cellulose, the most abundant organic polymer on earth. The cellulase (TSC; EC 3.2.1.4) from an alkalothermophilic Thermomonospora sp. has a low molecular weight of 14.2 kDa. It is optimally active at 323 K and stable over the wide pH range of 5 - 9. Moreover, it has bifunctional activity against cellulose and xylan polymers. In this study, TSC was purified from the native source and crystallized by the hanging-drop vapour-diffusion method. The crystals belong to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 49.9